Arteriovenous Malformation in the Auricle in a 59-Year-Old Woman - Junhui Jeong (Case Reports in Otolaryngology)
Arteriovenous malformation (AVM) is a vascular lesion with a direct communication between an artery and a vein without a capillary system. AVM primarily occurs in the intracranial area, but can also occur in the extracranial area. If there is a tender mass with pulsation or recurrent bleeding in the auricle, AVM should be considered even though it rarely occurs in the auricle. AVM in the ear should be managed carefully because the skin is thin in the ear, the cartilage could be involved, and progressive growth or inappropriate management could cause bleeding, infection, and cosmetic problems such as deformity. I present a case of a 59-year-old woman with AVM in the auricle.